Membongkar praktik kawin friend para wanita Sosialita di Surabaya - Nasiri Nasiri (State Institute of Islamic Studies (IAIN) Salatiga, 2018)
This research departed from three questions. The first, how does the practice of marriage friend for careers women in Surabaya? The second, why the practice of marriage friend for careers women in Surabaya? The third, how about Islamic law seen marriage friend practices for careers women in Surabaya? In order to answer the questions above, researcher conducted a qualitativer research using cass aproach. The necessary data of this study was collected by interview, observation, and revier of documentation. In order to articulate construction of careers women in Surabaya, whhich has collected data were analyzed using an inductive method. The results of this study indicate that there are two models of friend marriage in Surabaya. First, they practice friend marriage by looking for potential husbands through friends or the mass media and looking for religious leaders who can marry them. In this marriage the woman frees her husband from all obligations. Second, they chose the practice of marrying friends by finding their own husband and after finding them married at a distant or foreign place and usually this marriage ended after having a child. There are two reasons that Surabaya socialite women choose the practice of marrying a friend. First, the reason for the manivest is where they conduct this friend's marriage to free husbands from all obligations. Second, the latent reason, where they do this friend's marriage solely to seek biological satisfaction. Jurisprudence scholars disagree in addressing the practice of friendship in Surabaya. Some allow it because they see the terms of the marriage pillar have been fulfilled. There are those who forbid this friend's marriage model, this is because of the motivation caused by this friend's practice. According to them, this friend's marriage model is no different from gigolo rental practices.